Oliver Henry, and Ute Kelp (eds) Tumulus as Sema. Space, Politics, Culture and Religion in the First Millennium BC - Sweeney, Naoíse Mac Sweeney (Journal of Greek Archaeology, 2017)
Tumulus as Sema is a weighty contribution to scholarship. With 755 pages of text and 377 of plates arranged into two hardbound volumes, its publication was an ambitious undertaking just in terms of sheer scale. The intellectual ambition that this volume represents, however, is even more impressive.